PENETAPAN KAWASAN ANDALAN SEBAGAI PUSAT PERTUMBUHAN PADA TINGKAT KABUPATEN/KOTA DI KALIMANTAN TIMUR - Dwi Dhasta Wahyuningtiyas (Jurnal Ekonomi Pembangunan, 2011)
The objective of this study was to identify how the patterns of economic growth was, to know what sector which was able to develop in an effort to determine development priorities, and analyze where the leading region as a center of economic growth on Regency/ city level in in East Kalimantan. While the supreme sector at regency/ city in East Kalimantan, based on the calculation of Location quotient (LQ) are supreme agricultural sector in the regency of Malinau, superior mining & quarrying sector in East Kutai regency, superior processing industry sector in Bontang City, the superior electricity sector, gas & water supply in the city of Tarakan, superior construction sector in the city of Balikpapan, trade, hotels & restaurants sector in the City of Tarakan, supreme transport & communications sector in Samarinda, the supreme financial, rental & services  company sector in Samarinda City, and superior services sector in Samarinda. The leading areas as growth center on regency/ city level in East Kalimantan were Balikpapan and Tarakan City.